Phytochemical composition and antioxidant activity of extracts of some medicinal plants in Tunisia - Athmouni, khaled; Belghith, Taheni; El Fek, Abdelfattah; Ayadi, Habib (International Journal of Pharmacology and Toxicology, 2016)
The aim of this study was to investigate the chemical composition of the best known plants biomarkers from the locality of Gafsa (Tunisia). Majority of investigated plants had high levels of phenolics and exhibited noteworthy antioxidant activity. The plants showing the highest antioxidant activities were P. angustifolia, T. garganica, G. alypum and L. multifida. P. angustifolia demonstrated by far the most potent antioxidant activity, as well as total phenolic and total flavonoids content. In flavonoid structure of the aerial parts of the related species, different amounts of rutin, myricetin, morin, quercetin and kaempferol together with ergosterol, stigma sterol and b-sitosterol as phytosterols, vitamin D, vitamin K, a-tocopherol and retinol as vitamins, and arabinose, fructose, glucose, sucrose and maltose as sugars were found. The mineral analysis was related to the existence of Ca, Na, K, Fe, Mn, Zn and Mg with different amounts in all of the nine tested species.